A study of design new method cutting metal plate lead / Abdull Hadi Salleh. - Salleh, Abdull Hadi (2009)
Stamping Technology is one ofthe manufacturing process that highly used in the manufacturing industrial. This project is presenting the study of Design New Method Cutting Metal Plate Lead model TRSB-30C. Current research that relate with stamping press is study of developed die design and also improvement the performance of mechanical press machine. CATIA the CAD software and Auto cad software that is used in this project is a tool as initial process to design product and component. This project has present the standard operating procedures of stamping press and improvement of die design.